2021
DOI: 10.1155/2021/5553029
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship between Artificial Intelligence-Based General Anesthetics and Postoperative Cognitive Dysfunction

Abstract: Postoperative cognitive dysfunction (POCD) refers to the complications of the central nervous system before and after surgery in patients without mental disorders. Many studies have shown that surgical anesthesia may cause POCD, especially in elderly patients. This article aims to study the relationship between artificial intelligence-based general anesthetics and postoperative cognitive dysfunction. This article first describes and classifies artificial intelligence, introduces its realization method, machine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…S100β protein mainly exists in glial cells of the central nervous system. When the blood-brain barrier and the central nervous system are damaged, the expression of S100β protein in peripheral blood and cerebrospinal uid can be detected [22] . Previous studies have found that S100β protein is a good marker of nerve injury, and the increased concentration of S100β protein in elderly patients after surgery may be related to the occurrence of POD [23] .…”
Section: Discussionmentioning
confidence: 99%
“…S100β protein mainly exists in glial cells of the central nervous system. When the blood-brain barrier and the central nervous system are damaged, the expression of S100β protein in peripheral blood and cerebrospinal uid can be detected [22] . Previous studies have found that S100β protein is a good marker of nerve injury, and the increased concentration of S100β protein in elderly patients after surgery may be related to the occurrence of POD [23] .…”
Section: Discussionmentioning
confidence: 99%
“…Journal of Healthcare Engineering has retracted the article titled “Relationship between Artificial Intelligence-Based General Anesthetics and Postoperative Cognitive Dysfunction” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%
“…Journal of Healthcare Engineering has retracted the article titled "Relationship between Artifcial Intelligence-Based General Anesthetics and Postoperative Cognitive Dysfunction" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%